Indonesian Government Policy in Forest and Land Fire Management - Fajar Khaify Rizky; Riadhi Alhayyan; D. Shahreiza (Budapest International Research and Critics University, 2022)
The 1945 Constitution has mandated that natural resources, including forests, are controlled by the state and used as much as possible for the prosperity of the people. Natural resources have a very important position for human life that must be maintained, preserved and managed properly. Regarding the management, the government must make policies on natural resources so that natural resources, including forests, are not damaged, including due to forest and land fires. Therefore, government policies are very important in the management and prevention of forest and land fires so that they do not occur and do not cause harm to the environment and society.